Combining periodic function

  • Thread starter ACLerok
  • Start date
  • #1
194
0
Given:
x(t) =
cos(2*pi*f1*t) 0 <= t < 4
cos(2*pi*f2*t) 4 <= t < 8
cos(2*pi*f3*t) 8 <= t < 12

f1, f2, and f3 are given as well

Would it be possible to combine all three of these conditions into one convenient equation or am I just dreaming? I tried using Matlab to concatenate the three graphs, but it won't give me an equation of it.
 
Last edited:

Answers and Replies

  • #2
HallsofIvy
Science Advisor
Homework Helper
41,833
961
I'm not sure what you mean by a "convenient" equation. What you have is a perfectly good function, You could use the "Heaviside step function" which is defined by H(x)= 0 if x<= 0, H(x)= 1 if x> 0.

Then f(t)= cos(2pi f1 t)+ ((cos(2pi f2 t)- cos(2pi f1 t))H(t-4)+ (cos(2pi f3 t)- cos(2pi f2 t))H(t-8).

for 0<= t<= 4, both t-4< 0 and t-8< 0 so both H(t-4) and H(t-8) are 0 and only the first term, cos(2pi f1 t), is non zero. For 4< t<= 8, t-4> 0 so H(t-4)= 1 but H(t-8) is still 0: f(t)= cos(2pi f1 t)+ cos(2pi f2 t)- cos(2pi f1 t)= cos(2pi f2 t). If 8< t<= 12, both t-4> 0 and t-8>0 so both H(t-4) and H(t-8) are 1. f(t)= cos(2pi f1 t)+ cos(2pi f2 t)- cos(2pi f1 t)+ cos(2pi f3 t)- cos(2pi f2 t)= cos(2pi f3 t).

But is cos(2pi f1 t)+ ((cos(2pi f2 t)- cos(2pi f1 t))H(t-4)+ (cos(2pi f3 t)- cos(2pi f2 t))H(t-8) better than what you have?
 

Related Threads on Combining periodic function

  • Last Post
Replies
2
Views
3K
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
2
Views
3K
  • Last Post
Replies
9
Views
801
  • Last Post
Replies
18
Views
7K
  • Last Post
Replies
5
Views
789
  • Last Post
Replies
12
Views
25K
  • Last Post
Replies
6
Views
978
  • Last Post
Replies
7
Views
4K
  • Last Post
4
Replies
78
Views
10K
Top